"I Don't Like Being Good!" Changing Behavior With Technology-Based Self-Monitoring. Issue 3 (September 2015) - Bruhn, Allison Leigh; Vogelgesang, Kari; Schabilion, Katherine; Waller, LaNeisha; Fernando, Josephine
Self-monitoring has a well-established literature base for improving the behavior of students with a range of ages and abilities. Whereas self-monitoring often involves technology for prompting self-monitoring procedures, to date, only a few studies have examined the use of technology for recording self-monitored behavior. To extend the literature in this area, the effects of technology-based self-monitoring were examined using an iPad application called SCORE IT in which students and teachers rate students' behavior and view automated graphs of progress toward goals. Using a baseline and intervention (ABAB) design to measure outcomes, improvements in behavior were established for both middle school participants—one with attention deficit hyperactivity disorder and another receiving noncategorical special education services for reading, math, and behavioral deficits. Findings, limitations, and recommendations for future research are discussed.